Leksem Aktivitas Tangan Menyakiti dalam Bahasa Jawa Dialek Desa Malangsuko Kecamatan Tumpang Kabupaten Malang - Utami, Sri (Jurnal Likhitaprajna, 2023)
This research aims to describe lexemes that refer to the activity of hurting hands in the Javanese language of Malangsuko village, Tumpang District, Malang Regency. The data in this paper are in the form of lexemes that refer to hand activities. This research is a type of qualitative descriptive research using research methods (Introspective), self-dreaming and interviews. The steps taken are 1) describing the activity of hurting hands in the Javanese language of Malangsuko village 2) describing the meaning components of each lexeme 3) see the same components in each lexeme 4) create a differentiation matrix for each lexeme 5) describe the status of the semantic features in the matrix with the symbols -, 0, and +. 6) conclude with a diagram based on the meaning component analysis that has been carried out. The results of the research show that "hurting" hand activities in the Javanese dialect of Malangsuko village can be divided into two groups, namely based on the generic meaning component and the tools used and three subgroups, namely hand activities that hurt the neck, hand activities that hurt the head and its parts, and hand activities that hurt the neck. hands hurt the body. There are 4 lexemes for hand activities that hurt the neck, consisting of 1 lexeme for activities using tools and 3 lexemes for activities for hurting the neck without using tools. There are 16 lexemes for the activity of hurting the head and its parts, consisting of 2 lexemes for the activity of hurting the head and its parts using tools and 14 lexemes for the activity of hurting the head and its parts without using tools. There are 16 lexemes for body harming activities consisting of 8 lexemes for body harming activities using tools and 8 lexemes for hand activities hurting the head and its parts without using tools.